2000
DOI: 10.1046/j.1365-2249.2000.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T cell repertoire in the liver of patients with chronic hepatitis C

Abstract: SUMMARYMany T cells infiltrate into the liver of patients with chronic hepatitis C (CH-C). They are believed to play a crucial role in the immunopathogenesis of hepatic inflammation, but their clonality and specificity are unknown. The aim of this study was to clarify the characteristics of these T cells. We analysed the complementarity-determining region (CDR)3 size lengths of T cell receptor (TCR) b-chains by size spectratyping, and determined the sequences of Vb CDR3 after subcloning Vb -specific polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
5
19
0
2
Order By: Relevance
“…Sing et al 25 compared the clonality of V ␤ T-cell receptor-bearing population in the liver and peripheral blood of patients with hepatitis B and found clonotypic expansions in 4 to 9 TCR V ␤ subfamilies, indicating a high restriction in the T-cell composition of liver-infiltrating lymphocytes. Similar experiments in hepatitis C and autoimmune hepatitis, 17,18,26 showed many skewed spectratype patterns in lymphocytes in the liver.Our results from the 4 cases of chronic hepatitis B and C for TCR-spectratyping analysis found a similarly highly skewed V ␤ pattern consistent with these published results (and validating our use of frozen tissue). In addition, we demonstrated that we could detect a similar skewed spectratype pattern in the livers of patients with HAA.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Sing et al 25 compared the clonality of V ␤ T-cell receptor-bearing population in the liver and peripheral blood of patients with hepatitis B and found clonotypic expansions in 4 to 9 TCR V ␤ subfamilies, indicating a high restriction in the T-cell composition of liver-infiltrating lymphocytes. Similar experiments in hepatitis C and autoimmune hepatitis, 17,18,26 showed many skewed spectratype patterns in lymphocytes in the liver.Our results from the 4 cases of chronic hepatitis B and C for TCR-spectratyping analysis found a similarly highly skewed V ␤ pattern consistent with these published results (and validating our use of frozen tissue). In addition, we demonstrated that we could detect a similar skewed spectratype pattern in the livers of patients with HAA.…”
supporting
confidence: 68%
“…14,15 Analysis of the T-cell repertoire in these cases has demonstrated clonal expansions, and conserved features of antigen specificity in many of these expansions are linked to the immunopathogenesis of viral hepatitis. [16][17][18] Corresponding information concerning the T-cell immune response in HAA in liver or blood is unreported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 An effective CTL response requires T-cell engagement with the costimulatory molecules CD86 and CD28. [52][53][54] Colony inhibition by CTL in trisomy 8 MDS (which express CD86 on CD34 cells; data not shown) indicates that progenitors from these patients are competent antigen-presenting cells and susceptible CTL targets.…”
Section: Discussionmentioning
confidence: 99%
“…Two T-cell clones from patient 1 were identified twice (clones 1-17 and 5-11) in the cells sorted with anti-BV2. The nomenclature used to refer to each clone (for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] indicates that clones 1 and 17, arbitrarily assigned these numbers when cultured in microtiter plates, turned out to be identical or sibs of each other on sequence analysis. One T-cell clone from patient 3 was also isolated twice (clone 3-7).…”
Section: T-cell Cloningmentioning
confidence: 99%